The Effect of Using English Speaking Practice Application on the First Year Students’ Speaking Ability at SMA S Adabiah Padang - Oktaviano, Rizky; Kher, Dinovia Fannil (Universitas Negeri Padang, 2024)
Many high school students were not interested in speaking. It is due to the difficulties to do so. However, there was a mobile phone application named English Speaking Practice application as the solution to those issues. This study aimed to investigate the effect of using English Speaking Practice application on the first year students’ speaking ability at SMAS Adabiah Padang.This study was a pre-experimental one sample pre-test post-test design. The population was all of 10th grade students at SMAS Adabiah Padang and the sample was 34 students of XE1 at SMAS Adabiah Padang chosen with cluster sampling technique. The instrument was a read-aloud speaking test adapted by Brown (2004). The data was analyzed by using SPSS. It was discovered that the sig. values was 0.001 less than 0.05 which means the hypothesis null was rejected. Therefore, the result of this study shown that there was an effect of using English Speaking Practice application on the first year students’ speaking ability at SMAS Adabiah Padang.